A Female with Recurrent Venous Thrombosis - Das, Aparna; Hoque, AKM Aminul; Dasgupta, Ratan; Kabir, Ahmedul; Banik, Gobinda; Huda, ANM Shamsul; Islam, Moinul (Journal of Medicine, 2012)
A 50- year-old female was presented with recurrent venous thrombosis with ischemic stroke due to protein S deficiency. Other causes of recurrent venous thrombosis were excluded by different investigations. We only found low level of protein S. In most of the cases, thrombophilia screening is not usaally done. So, this report will illustrate the importance of thrombophlia screening in patient having recurrent venous thrombosis. DOI: http://dx.doi.org/10.3329/jom.v13i1.10085 JOM 2012; 13(1): 100-102